Influence of social cognition as a mediator between cognitive reserve and psychosocial functioning in patients with first episode psychosis. Issue 16 (22nd December 2020) - González-Ortega, I; González-Pinto, A; Alberich, S; Echeburúa, E; Bernardo, M; Cabrera, B; Amoretti, S; Lobo, A; Arango, C; Corripio, I; Vieta, E; de la Serna, E; et al.
Abstract: Background: Social cognition has been associated with functional outcome in patients with first episode psychosis (FEP). Social cognition has also been associated with neurocognition and cognitive reserve. Although cognitive reserve, neurocognitive functioning, social cognition, and functional outcome are related, the direction of their associations is not clear. Therefore, the main aim of this study was to analyze the influence of social cognition as a mediator between cognitive reserve and cognitive domains on functioning in FEP both at baseline and at 2 years. Methods: The sample of the study was composed of 282 FEP patients followed up for 2 years. To analyze whether social cognition mediates the influence of cognitive reserve and cognitive domains on functioning, a path analysis was performed. The statistical significance of any mediation effects was evaluated by bootstrap analysis. Results: At baseline, as neither cognitive reserve nor the cognitive domains studied were related to functioning, the conditions for mediation were not satisfied. Nevertheless, at 2 years of follow-up, social cognition acted as a mediator between cognitive reserve and functioning. Likewise, social cognition was a mediator between verbal memory and functional outcome. The results of the bootstrap analysis confirmed these significant mediations (95% bootstrapped CI (−10.215 to −0.337) and (−4.731 to −0.605) respectively). Conclusions: Cognitive reserve and neurocognition are related to functioning, and social cognition mediates in this relationship.